Applied biomechanics within the Kinesiology discipline in higher education - Vladimir Potop; Liviu E. Mihailescu; Ion Mahaila; Monika Zawadka-Kunikowska; Wladyslaw Jagiello; Andrii Chernozub; Mihai – Sebastian Baican; Olivia Carmen Timnea; Carmen Ene-Voiculescu; Alexandru Ascinte (Physical Education of Students)
Background and Study Aim. Biomechanics is a fundamental component of Kinesiology, offering critical insights into the mechanics of human movement. As the demand for comprehensive educational programs in Kinesiology grows, understanding the role and effectiveness of biomechanics within these programs becomes increasingly important. The aim of the study is to investigate and highlight the role and importance of biomechanics in the context of higher education, with an emphasis on the discipline of Kinesiology.